Benefits of macroscopic on-site evaluation in endoscopic ultrasound-guided tissue acquisition for comprehensive genomic profiling - Sato, Junya; Ishiwatari, Hirotoshi; Ishikawa, Kazuma; Sakamoto, Hiroki; Doi, Takuya; Yamamura, Masahiro; Takada, Kazunori; Yamamoto, Yoichi; Yoshida, Masao; Ito, Sayo; Kawata, Noboru; Imai, Kenichiro; Hotta, Kinichi; Ono, Hiroyuki (Endoscopy International Open, 2025)
Matched therapy based on comprehensive genomic profiling is a potential treatment option for patients with inoperable pancreatic cancer; however, the optimal method for obtaining tissue samples suitable for comprehensive genomic profiling using endoscopic ultrasound-guided tissue acquisition remains unclear. This study aimed to determine the optimal endoscopic ultrasound-guided tissue acquisition method to obtain samples for comprehensive genomic profiling.This retrospective study included 86 consecutive patients with pancreatic cancer who underwent comprehensive genomic profiling using FoundationOne CDx (Foundation Medicine Inc.) and endoscopic ultrasound-guided tissue acquisition between June 2019 and January 2023. Macroscopic visible core length was measured using on-site macroscopic evaluation in all patients. Foundation Medicine Inc. reported analysis results categorized as passed (successful FoundationOne CDx), qualified, or failed. We investigated factors predicting successful FoundationOne CDx treatment.Needles sized 22, 20, and 19 gauge were used in 63, one, and 23 patients, respectively. The stylet slow-pull and suction techniques were performed in 43 and 41 patients, respectively. Median total macroscopic visible core length in the formalin-fixed paraffin-embedded blocks subjected to FoundationOne CDx was 41 mm. The success rate for FoundationOne CDx was 66%. Multiple linear regression analysis revealed that macroscopic visible core length independently affected successful FoundationOne CDx (P = 0.0019).In tissue specimens obtained using endoscopic ultrasound-guided tissue acquisition, macroscopic visible core length can be associated with an appropriate sample for FoundationOne CDx.
Keywords: Endoscopic ultrasonography; Pancreas; Tissue diagnosis